18F-FLUORODEOXYGLUCOSE POSITRON EMISSION TOMOGRAPHY COMBINED WITH COMPUTED TOMOGRAPHY IN EVALUATION OF EFFECTIVENESS OF TARGETED THERAPY OF RADIOACTIVE IODINE-REFRACTORY DIFFERENTIATED THYROID CANCER (CLINICAL OBSERVATION) - A. A. Odzharova; M. B. Dolgushin; A. M. Mudunov; I. S. Romanov; R. E. Tulin; D. I. Nevzorov (Опухоли головы и шеи, 2017)
N.N. Blokhin National Medical Research Oncology Center, Ministry of Health of Russia; 24 Kashirskoe Shosse, Moscow 115478, Russia Positron emission tomography (PET) with 18F-fluorodeoxyglucose is included in the algorithm of examination and monitoring in patients with radioactive iodine-refractory differentiated thyroid cancer. In assessing the effectiveness of targeted therapy, criteria based on the values of SUVmax (standardized uptake value) in metastases are used. The article shows the results of PET studies in a patient with radioactive iodine-refractory papillary thyroid cancer treated with sorafenib. The dynamics of tumor activity of metastases by different quantitative indicators were evaluated.